2017
DOI: 10.1007/978-3-319-46966-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel SOFC Tri-generation System for Building Applications

Abstract: i AbstractIn response to the critical need to decarbonise the built environment, alternative methods for more effective energy utilisation need to be explored including trigeneration systems.Tri-generation is the simultaneous generation of electricity, heating and/or cooling from a single fuel source. Solid oxide fuel cell (SOFC) and liquid desiccant demonstrate many characteristics that make them an attractive option in the development of an efficient and effective tri-generation system. SOFCs have high opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 81 publications
(163 reference statements)
0
10
0
Order By: Relevance
“…The main capacity of LDAC systems is their ability in dealing with moisture removal. However, their ability to deal with sensible loads is fairly limited [40,41]. For this reason, the integration of liquid desiccant systems with systems able to control the supply air temperature has been crucial for the worldwide marketability of liquid desiccant systems.…”
Section: Energy Use Of Liquid Desiccant Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main capacity of LDAC systems is their ability in dealing with moisture removal. However, their ability to deal with sensible loads is fairly limited [40,41]. For this reason, the integration of liquid desiccant systems with systems able to control the supply air temperature has been crucial for the worldwide marketability of liquid desiccant systems.…”
Section: Energy Use Of Liquid Desiccant Systemsmentioning
confidence: 99%
“…The simultaneous production of power, heating and cooling obtainable by the combination of liquid desiccant technology with CHP systems is one of the most promising, particularly for applications where the humidity removal is fundamental [41]. Recent studies also showed the feasibility of the coupling of fuel cells with liquid desiccant technology [40,49]. Elmer [40] investigated the feasibility of using a Solid-Oxide Fuel Cell (SOFC) to produce electricity and drive the regeneration process of the liquid desiccant, while Kim et al [49] investigated the integration of the liquid desiccant system with a Proton Exchange Membrane Fuel Cell (PEMFC).…”
Section: Energy Use Of Liquid Desiccant Systemsmentioning
confidence: 99%
See 3 more Smart Citations